2011
DOI: 10.1038/nature10263
|View full text |Cite
|
Sign up to set email alerts
|

Direct conversion of mouse fibroblasts to hepatocyte-like cells by defined factors

Abstract: The location and timing of cellular differentiation must be stringently controlled for proper organ formation. Normally, hepatocytes differentiate from hepatic progenitor cells to form the liver during development. However, previous studies have shown that the hepatic program can also be activated in non-hepatic lineage cells after exposure to particular stimuli or fusion with hepatocytes. These unexpected findings suggest that factors critical to hepatocyte differentiation exist and become activated to induce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

32
719
3
5

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 757 publications
(759 citation statements)
references
References 31 publications
32
719
3
5
Order By: Relevance
“…These factors were discovered from pools of many transcription factors involved in liver development; the common component was FoxA. However, compared with primary hepatocytes, iHeps show significant differences in gene expression and are unable to fully rescue liver function in a transplantation model (Huang et al 2011;Sekiya and Suzuki 2011). CellNet analysis, which is a bioinformatics tool to assess the fidelity of cell conversion, surprisingly revealed that iHeps induced by FoxA and HNF4a represent gut endoderm progenitors more than mature hepatocytes .…”
Section: Espinosa and Emerson 2001mentioning
confidence: 99%
See 1 more Smart Citation
“…These factors were discovered from pools of many transcription factors involved in liver development; the common component was FoxA. However, compared with primary hepatocytes, iHeps show significant differences in gene expression and are unable to fully rescue liver function in a transplantation model (Huang et al 2011;Sekiya and Suzuki 2011). CellNet analysis, which is a bioinformatics tool to assess the fidelity of cell conversion, surprisingly revealed that iHeps induced by FoxA and HNF4a represent gut endoderm progenitors more than mature hepatocytes .…”
Section: Espinosa and Emerson 2001mentioning
confidence: 99%
“…Another example of transdifferentiation across germ layers is when hepatocyte-like cells are induced from fibroblasts (iHep) by exogenous expression of either forkhead box protein A1 (FoxA1), FoxA2, or FoxA3 with HNF4a (Sekiya and Suzuki 2011) or exogenous expression of FoxA3, GATA4, and HNF1a in combination with the inactivation of the tumor suppressor gene p19 Arf (Huang et al 2011). These factors were discovered from pools of many transcription factors involved in liver development; the common component was FoxA.…”
Section: Espinosa and Emerson 2001mentioning
confidence: 99%
“…Japanese research teams 8 were screening the effects of twelve transcription factors for conversion of mouse embryonic and adult fibroblasts into hepatocyte like cells, finally they found three specific combinations of two transcription factors, comprising Hnf4a plus Foxa1, Foxa2 or Foxa3 is sufficient for generation of hepatocyte like cells. In the same time, Chinese research teams 9 reported in independently that new cocktails of transcription factors of Gata4, HNF1alpha, Foxa3, and RNAi-mediated inactivation of p19Arf for direct induction of functional hepatocyte like from mouse tail-tip fibroblasts.…”
Section: Commentsmentioning
confidence: 99%
“…Recently, researchers used such liver specific transcription factors for generation of hepatocyte cells from skin fibroblast cells in vitro. [8][9][10][11][12] The ultimate aim of generation of hepatocytes from skin cells to treat liver diseases. If we know the transcription factors and small molecules which have potential to convert hepatocyte from fibroblast, why not to explore transcription factors and small molecules in vivo directly to repair or regenerating the tissue or organs.…”
Section: Commentsmentioning
confidence: 99%
“…For instance, overexpression of different sets of transcription factors or microRNAs was shown to convert fibroblasts into macrophages, 2 cardiomyocytes, 3 neuronal cells, 4,5 blood cells, 6 and hepatocytes. 7 The principle of both, reprogramming of somatic cells to pluripotent state and direct conversion to specific cell types is similar and based on forced overexpression of defined master-genes (transcription factors and/or microRNAs), which activate downstream gene networks specific for a desired cell type. However, the mechanisms of these processes have not been completely studied yet.…”
Section: Introductionmentioning
confidence: 99%